The return on investment for education in Pakistan - Raima Nazar; Imran Sharif Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The study provides estimates of the private returns to education in Pakistan by using a random sample of 850 wage earners including male and female from different professions between age group 15-65 years from Multan district. This study provided a novel contribution by providing an in-depth analysis of return on investment for education by focusing on both aspects of education like quantity and quality of education and in case of quantity, education is treated both as a continuous and discrete variable. By using ordinary least square technique and by following the procedure of Mincer earning function this study examined the earning disparities due to gender, location (rural-urban), marital status, medium of instruction and found that female wage earners have higher returns to education. Similarly, people living in urban areas enjoy high returns to investment in education. Due to greater job mobility unmarried workers get higher returns while in case of levels of education returns increases gradually. In case of qualitative returns we found that English medium of instruction plays a highly significant and positive role in earnings.
Keywords: 330; return on human capital; return on investment; university education; secondary education; primary education